Perbandingan Hasil Gambaran Acromioclavicular Joint dengan Menggunakan Proyeksi AP Beban 3 Kg dengan AP Tanpa Beban - Muh Amirul Mukminin; Hesti Andriyani Putri; Via Rahmah (Lembaga Pengembangan Kinerja Dosen, 2026)
Radiographic examination plays a crucial role in visualizing internal body structures for diagnostic purposes. One of the radiographic assessments frequently performed is the Acromioclavicular (AC) joint projection, which is used to evaluate abnormalities such as joint widening, subluxation, and dislocation. This study aimed to compare the image quality of the AC joint using the Anteroposterior (AP) projection with a 3-kg load and without load. The study was conducted in the Radiology Laboratory of STIKES Borneo Nusantara using a conventional X-ray system with a quantitative descriptive case-study approach. Data were collected through observation and questionnaires administered to 10 research subjects, including radiographers and patient participants. The findings demonstrated that the AP projection with a 3-kg load produced clearer visualization of the AC joint, particularly in widening of the joint space and separation between the humeral head and glenoid cavity. The average image quality score using load was 3.5 (good), compared with 2.9 (poor) for the projection without load. The study concludes that applying a 3-kg load improves anatomical visualization of the AC joint and is recommended for cooperative patients to enhance diagnostic accuracy.